The greatest love story ever told [compact disc, unabridged] - Mullally, Megan; Offerman, Nick, 1970- (Penguin Audio, 2018)
The popular comedic couple trace the story of their relationship, sharing anecdotes and secrets that reveal how they overcame considerable social differences through their shared values and mutual love of music and laughter.